Thermal properties of alkaline and alkaline-earth borate glasses - Adamiv, V.T.; Burak, Ya.V.; Girnyk, I.S.; Teslyuk, I.M. (Functional Materials, 2013)
Results of dilatometric (80–800 K) and DTA (293–1200 K) investigations of borate glasses Li₂B₆O₁₀, LiCsB₆O₁₀, Li₂B₄O₇, LiKB₄O₇, LiCaBO₃ and CaB₄O₇ in temperature range have been presented. Thermal parameters Tg, TD, Tp, Tm and temperature dependences of thermal expansion coefficient α(T) have been determined and analyzed. It was ascertained that ratios BO₃/BO₄, as well as radius and charge of the cations, have an influence on the thermal parameters of the borate glasses.